THE LEGAL STATUS OF DIGITAL BANKS IN INDONESIA - Elsa Assari (Fakultas Syariah, 2022)
The bank digital concept is designed so the customer can independently do the transaction, make an online account, get online information, close the account, and so forth. Norm text wise, digital bank is not present in the positive law of banking in Indonesia. So, the problem is about the legal basis of digital banks in the country. The researchers discuss the problem by applying normative juridical method with statute and analytical approaches. The primary law sources are from the laws and regulations, the court’s transcript of proceedings, and the court decision. The secondary sources are previous research results and legal articles. The analysis technique of legal sources implements systematic interpretation. The results show that the legal basis for digital banks in Indonesia is implicitly written on Banking Law and POJK No. 12/POJK.03/2021 concerning Commercial Banks. Digital banks must be an Indonesian legal entity bank and acquire a license from the OJK. Digital banks should be clearly differentiated with other Indonesian legal entities by applying a better and more complete regulation to give legal certainty, protect the customer’s personal data, and avoid data leakage. This article hopefully can be a reference for regulating digital banking in Indonesia.Konsep bank digital dirancang agar nasabah dapat melakukan transaksi secara mandiri, membuka rekening online, memperoleh informasi online, menutup rekening dan kebutuhan lainnya. Bank digital secara teks norma tidak terdapat dalam hukum positif perbankan di Indonesia. Persoalan yang muncul adalah bagaimanakah dasar hukum pengaturan bank digital di Indonesia. Penulis melakukan pembahasan dengan menggunakan metode penulisan yuridis normatif dengan pendekatan perundang-undangan dan pendekatan analitis. Bahan hukum utama yang digunakan meliputi peraturan perundang-undangan, berita acara persidangan, dan putusan pengadilan. Bahan hukum sekunder meliputi hasil penelitian dan artikel hukum. Teknik analisis bahan hukum menggunakan tafsir sistematis. Hasil penelitian menunjukkan bahwa dasar hukum bank digital di Indonesia secara implisit diatur melalui Undang-Undang Perbankan dan POJK No. 12/POJK.03/2021 tentang Bank Umum. Bank digital harus berbadan hukum Indonesia dan mendapat izin dari Otoritas Jasa Keuangan. Bank digital harus dibedakan secara jelas dengan badan hukum Indonesia melalui penggunaan payung hukum yang lebih baik dan lengkap guna memberikan kepastian hukum, terlindunginya data pribadi konsumen serta risiko kebocoran data. Artikel ini bermanfaat untuk dijadikan sebagai dasar rujukan pengaturan perbankan digital di Indonesia.